COMMUNITY RELATIONS MILLENIAL CONTENT CREATOR IN FORMING A BRAND IMAGE - Delinda Shisma Praswary; Gede Sri Darma (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Community Relations is a program from the company for the community. By carrying out these aspects, it is impossible to form a positive image for the company. In addition, to form a brand image in the current digital era, companies can take advantage of millennial content creators. Each company has participated in building the country, is responsible for the nation and society, for the welfare of shareholders, possible investors, employees, managers, business partners, the government and the surrounding environment. PT. Cellular Telecommunications (Telkomsel) through the Telkomsel Apprentice Program (TAP) Denpasar Branch. This study aims to examine whether the activities of community relations and millennial content creators can form a positive image of the community. The method used in this study is a qualitative approach with purposive sampling. In this study, the collection process was carried out through a process of interviews with resource persons as well as observation and documentation. In this study, public relations and millennial content creators were able to build and maintain a positive image of the company, especially the surrounding community, during the implementation of these activities, the Denpasar Telkomsel Branch covered issues of fact gathering, action planning and communication as well as the evaluation phase.